2016
DOI: 10.18632/oncotarget.13649
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 contributes to radioresistance and cancer stemness of head and neck cancer by regulating cellular reactive oxygen species via a SMAD-associated signaling pathway

Abstract: Radiotherapy is an integral part for the treatment of head and neck cancer (HNC), while radioresistance is a major cause leads to treatment failure. GDF15, a member of the TGF-β superfamily, is hypothesized to participate in various types of homeostasis. However, the potential role of this molecule in regulation of radiosensitivity remains unclear. In this study, we demonstrated that GDF15 contributed to radioresistance of HNC, as determined by both gain- and lost-of-functional experiments. These results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 66 publications
1
52
0
Order By: Relevance
“…In endothelial cells, GDF15 overexpression leads to cellular senescence by increasing oxidative stress, whereas GDF15 knockdown reversed IR-induced cellular senescence 31 . In head and neck cancer cells, however, GDF15 was reported to contribute to radioresistance and cancer stemness by decreasing ROS via a SMAD-associated signaling pathway 43 , 44 . We confirmed that the functions of GDF15 in HSG human salivary gland epithelial cells are similar to that in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, GDF15 overexpression leads to cellular senescence by increasing oxidative stress, whereas GDF15 knockdown reversed IR-induced cellular senescence 31 . In head and neck cancer cells, however, GDF15 was reported to contribute to radioresistance and cancer stemness by decreasing ROS via a SMAD-associated signaling pathway 43 , 44 . We confirmed that the functions of GDF15 in HSG human salivary gland epithelial cells are similar to that in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…GDF15 plays multifunctional roles in context of diverse physiological and pathological conditions including proliferation, apoptosis, senescence, stemness, obesity, inflammatory response, and malignancies. It has been shown that in the early stage of cancer, GDF15 can induce tumour cells apoptosis, and at late stages, GDF15 production will help metastases and tumour progression . It has been reported that GDF15 contributes to induce apoptosis in various cell lines including A549 lung adenocarcinoma, and lower level of GDF15 in malignant gliomas has reduced cell proliferation and tumorigenesis, suggesting the contribution of GDF15 to cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in the early stage of cancer, GDF15 can induce tumour cells apoptosis, and at late stages, GDF15 production will help metastases and tumour progression. 3,[5][6][7] It has been reported that GDF15 contributes to induce apoptosis in various cell lines including A549 lung adenocarcinoma, 8,9 and lower level of GDF15 in malignant gliomas has reduced cell proliferation and tumorigenesis, 10 suggesting the contribution of GDF15 to cancer progression. Interestingly, in the oral squamous cell carcinoma (OSCC), the TGFBR2 is downregulated, 11 and GDF15 in OSCC has no apoptotic effect and inhibits caspase activity.…”
mentioning
confidence: 99%
“…These findings suggest that GDF15 may act as a cardio-protective factor via suppression of the DOX-induced cell death of hiPSC-CMs mediated by generation of ROS and/or suppression of the p53 signaling apoptosis pathway. In this context, it was shown that GDF15 contributes to radioresistance of cancer cells by suppressing cellular ROS [59]. Moreover, it was also suggested that GDF15 inhibits endothelial cell apoptosis in response to high glucose by inhibiting ROS overproduction [60].…”
Section: Is It Possible To Identify Common Factors Playing a Role In mentioning
confidence: 99%